Recurrent TERT promoter mutations in urothelial carcinoma and potential clinical applications - Kurtis, Boaz; Zhuge, Jian; Ojaimi, Caroline; Ye, Fei; Cai, Dongming; Zhang, David; Fallon, John T.; Zhong, Minghao (Annals of diagnostic pathology, 2016)
Increased telomerase activity is associated with almost all types of advanced human cancers with unknown molecular mechanism(s). Two recurrent point mutations in the promoter region of telomerase reverse transcriptase (TERT)—the key subunit of telomerase—have recently been identified in melanoma as well as a small sample of bladder cancer cell lines. However, the incidence and clinical-pathological significance of these mutations in urothelial carcinoma have not been well established yet. We collected 86 specimens of urothelial carcinoma including upper and lower urinary tract: high grade and low grade, invasive and noninvasive, and primary and metastatic. We also included some matched benign urothelium and common benign bladder lesions: cystitis, nephrogenic adenoma, and inverted papilloma. In addition, we collected urine samples for urothelial carcinoma workup; blood samples from patients underwent cystectomy with extensive lymphovascular invasion. All specimens were subject to polymerase chain reaction amplification and bidirectional Sanger sequencing for the TERT promoter mutations: C228T and C250T. We found that 64 (74%) of 86 carcinoma samples harbored 1 of the 2 TERT promoter mutations (C228T, n = 54; C250T, n = 10); the incidences were roughly equal regardless of site of origin, histologic grade, and invasive status. All matched benign and benign lesion samples showed wild-type sequence. These TERT promoter mutations are the most common genetic alterations in urothelial carcinoma and are not associated with tumor locations, grade, or invasiveness. Importantly, the feasibility of detecting these mutations in urine samples may provide a novel method to detect urothelial carcinoma in urine.